Deutsch lernt man meistens auf Niederländisch. Zielsprachengebrauch im schulischen Fremdsprachenunterricht in den Niederlanden. German you learn mostly in Dutch. Target language use in language teaching at schools in the Netherlands - Jentges, Sabine (Glottodidactica, 2016)
Teaching German as a foreign language in the Netherlands is mostly contrastive in nature – at all language levels. It is repeatedly argued that this is due to the close proximity of the two languages. Therefore, Dutch GFL textbooks use both target and source language throughout. At the same time, both learners and teachers repeatedly state that too little German is spoken in GFL-teaching in the Netherlands. This paper discusses the target language use at schools in the Netherlands by critically analysing (a selection of) GFL teaching materials. And the situation of German teaching in general.